-3=m-3

Simple and best practice solution for -3=m-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=m-3 equation:


Simplifying
-3 = m + -3

Reorder the terms:
-3 = -3 + m

Add '3' to each side of the equation.
-3 + 3 = -3 + 3 + m

Combine like terms: -3 + 3 = 0
0 = -3 + 3 + m

Combine like terms: -3 + 3 = 0
0 = 0 + m
0 = m

Solving
0 = m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1m' to each side of the equation.
0 + -1m = m + -1m
Remove the zero:
-1m = m + -1m

Combine like terms: m + -1m = 0
-1m = 0

Divide each side by '-1'.
m = 0

Simplifying
m = 0

See similar equations:

| 3=l-5 | | 4n-2n+10=22 | | -9+y=7 | | f(x)=x^2+9x-1 | | 1.05t+0.63=-0.07t | | 4x+2(8)=4x(9) | | 10n+2=22 | | 13-6b=3+11b | | 9n+18=36 | | (99+x)=(176+y) | | -9(x+3)+3x+6=5x+9 | | 6.75t+7=15.5t+14 | | 4568b-4=7 | | -v+2=3 | | 116=-4(-4y)-9(2y)+y | | (w*3-9)+(w+4)=(w*3-9)+(w+4) | | 2x+3y=5.13 | | 16+b^2+6b=0 | | 4y^6(y^2+9y+2)= | | 8n^2-3n-16=24 | | -10+3x=-4 | | X+y=y+x+200 | | 57=3v+3 | | 89-116=-4(-4y)-9(2y) | | 4x+6+6x=36 | | x+y+z=2000zxy | | (7x-4x)=y | | -5x-2=-2x-17 | | 0.5(2n-10)=22 | | -4x+5+6x=37 | | 183=3+10x | | 20+x*-4=44 |

Equations solver categories